Applying game theory to volleyball strategy - Lin, K. (International Journal of Performance Analysis in Sport, 2014)
Mottley (1954) asserted that applying scientific methods to developing sports strategies could substantially improve team's performance. Developing an effective volleyball strategy is a sought-after goal of volleyball players and a crucial aspect of team success. This study was focused on applying game theory to construct a volleyball strategy for players to use before a game and to adjust the guidelines included in the strategy during the game. The game theory analysis indicates that no pure Nash equilibrium existed. An analysis of mixed strategy equilibrium provided a set of possibility formulas for arriving at an optimal volleyball strategy. Volleyball players can follow the strategy formulas to perform favorably before the game and make corresponding adjustments based on situational changes during the game. The results indicate that game theory can provide volleyball coaches and players with effective instruction to execute their game plan throughout the competition.